Faktor yang mempengaruhi Public Satisfaction di Kelurahan Beringin Raya: Factors influencing public satisfaction in Beringin Raya Subdistrict - Yulian Sari; Khaidarmansyah Khaidarmansyah (OGZ Research & Publishing, 2026)
Objective: This study aims to determine the importance of the variables in serving public satisfaction in the Beringin Raya sub-district. Methodology: This study applies a quantitative approach and uses multiple linear regression with SPSS 26 analysis tools. Research Results: Partially, Managerial Support and Quality of Service variables have a significant effect on public satisfaction, while Work Discipline does not. Simultaneous results show that all variables have an effect on public satisfaction. The R-square value in this study is 70%, with the remainder outside of this study.